1991
DOI: 10.1111/j.1365-2621.1991.tb04732.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Three Cholesterol Oxidation Products in Raw Meat and Chicken

Abstract: Raw veal, beef, pork, and chicken muscle tissues were extracted by a modified dry column. procedure in which silicic acid was incorporated in the trap of the column. This method separated cholesterol derivatives from the bulk of neutral lipids, phospholipids and cholesterol. Isolation of sterols by preparative thin layer chromatography followed by quantification by direct on-column capillary gas chromatography permitted measurement of 7-ketocholesterol, cholesterol 501, 6u-epoxide, and cholesterol 5P,6P-epoxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 19 publications
2
22
1
Order By: Relevance
“…Furthermore, the amounts of cholesterol oxides obtained in raw meat agreed with those reported by Zubillaga and Maerker (30). Artifact production was minimized by taking strict precautions such as using butylated hydroxytoluene (0.002%) during the extraction procedure, avoiding elevated temperatures (>40ºC) during sample handling, and storing at low temperatures for very short periods.…”
Section: Resultssupporting
confidence: 61%
“…Furthermore, the amounts of cholesterol oxides obtained in raw meat agreed with those reported by Zubillaga and Maerker (30). Artifact production was minimized by taking strict precautions such as using butylated hydroxytoluene (0.002%) during the extraction procedure, avoiding elevated temperatures (>40ºC) during sample handling, and storing at low temperatures for very short periods.…”
Section: Resultssupporting
confidence: 61%
“…The meat was irradiated at 4°C to a dose of 10 kGy. Although the COPS distribution patterns produced by y-radiation in model systems have been reported to be different from those generated by autoxidation (Maerker andJones, 1991, 1993), the same results were not observed between irradiated and unirradiated, fresh or stored meats (Zubillaga and Maerker, 1991;Hwang and Maerker, 1993). This dissimilarity of behavior of cholesterol in model membranes and in meat was probably attributable to the complexity of the meat systems (Hwang and Maerker, 1993).…”
Section: Effect Of Irradiationcontrasting
confidence: 75%
“…Zubillaga and Maerker (199 1) analyzed the irradiated meat for 7-ketocholesterol and the epoxides and found that all 3 cholesterol oxidation products increased over 3-wk storage. 7-Ketocholesterol was the principal product and constituted well over 50% of the mixture (Zubillaga and Maerker, 1991). While the recovery of 7-ketocholesterol and cr-epoxide was -97%, the recovery of B-epoxide was only 62%.…”
Section: Cholesterol Oxides In Meat and Meat Productsmentioning
confidence: 99%
“…Monahan et al (1992) demonstrated that the rate of cholesterol oxidation in pork is greatly accelerated during storage following cooking and appears to follow the same trend as lipid oxidation in general. Zubillaga and Maerker (1991) reported that the predominant species was reported to be 7-ketocholesterol, accounting for almost half of the total COPs, followed by 7a-and 7b-hydroxycholesterol and both epoxides in order of decreasing concentration. Oxidation reactions are initiated in the highly susceptible membrane bound phospholipids, which contain relative large amounts of polyunsaturated fatty acids.…”
Section: Meat Productsmentioning
confidence: 98%